The Influence of Current Ratio and Solvency on Financial Performance at PT. Adaro Energy Indonesia Tbk Period 2015-2024 - M Aab Abdurrahman; Tedi Pitri (Formosa Journal of Social Sciences (FJSS), 2024)
This study was conducted to understand the impact of current ratios and solvency on currency workforce performance. This research was conducted at PT. Adaro Energy Indonesia, Tbk during the 2015-2024 period. The research method used in this research combines quantitative research design with associative descriptive. The population in this research is secondary data from PT's financial reports. Adaro Energy Indonesia., Tbk. The sample was taken using a non-probability sampling technique using purposive sampling with certain criteria, namely the quarterly financial report of PT. Adaro Energy Indonesia., Tbk 2015-2024. To carry out sensitivity analysis, one can use coefficient of determination analysis, hypothesis testing using t and f tests, and sensitivity line analysis. Based on the completed analysis, it is determined that the current ratio determination coefficient for labor participation is 0.292, which is included in the medium category, and the solvency coefficient for determining participation is 0.565, which is included in the medium category. Based on the completed specified analysis, it is shown that the significant contribution of the independent variables (solvency and current ratio) to the dependent variable (working capital) is approximately 44%, with the remaining 56% explained by other variables not examined by the researchers